Study on the Test System Design and the Test Method for Gearbox Housing Deformation - Zou Xihong; Liu Yu; Peng Jigang; Liu Chunlin; Luo Yang (Jixie chuandong)
Taking a casting aluminum alloy gearbox as the research object,a high precision and easy to control gearbox housing deformation test system is designed by the mode of hydraulic servo control. The test system can also be used for the torsion test of various transmission parts,such as a transmission shaft,a clutch,etc. by properly configuring the corresponding fixture. In order to comprehensively consider the dynamic and static deformation process of the gearbox,a loading method of variable slope and variable amplitude is used to establish a simple and easy method for deformation test of gearbox. The feasibility of the deformation test system and the test method of the gearbox is verified by the test that combined with an enterprise gearbox. And this not only provides an important means for the deformation test of the gearbox,but also provides the accurate basic data for the transmission shell stiffness and NVH design,analysis and optimization.